(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The present study was designed to determine the anti-testicular activity of hydro-ethanol seed extract of Areca catechu (10, 20 and 40 mg) in dose-dependent fashion in albino rats. Seminal vesicular fructose (SVF), oxidative stress sensors, gene expression, somatic weight, reproductive organo-somatic indices, spermiological, hormonal profile, and testicular histological examination for qualitative and quantitative investigations of spermatogenesis were observed. In compared to the placebo treated control (PTC), the exposure of the said doses showed a statistical significant downward deviation in the spermiological, hormonal, SVF profile, kinetics of testicular key androgenic dehydrogenase enzymes, and diameters of seminiferous tubules. Anti-oxidant enzyme kinetics were reduced significantly against PTC, and the quantity of malondialdehyde in male gonad and sperm precipitate was elevated in significant level (p<0.05). Expression of apoptotic promoting gene in testis was increased (p<0.05) and anti-apoptotic Bcl-2 gene expression exhibited a significant decrease (p<0.05) in treated group comparison to the PTC. The alterations in the activities of phosphatases in hepatic tissue was not significant from the background of PTC suggesting that the plant has no systematic undesirable effect in physiological processes. The observation highlighted that 10 mg dose as the threshold dose for imposition of such anti- testicular activity leading to male contraception.